Indirect Optimization of Satellite Deployment into a Highly Elliptic Orbit - Francesco Simeoni; Lorenzo Casalino; Alessandro Zavoli; Guido Colasurdo (International Journal of Aerospace Engineering)
The analysis of the optimal strategies for the deployment of a spacecraft into a highly elliptic orbit is carried out by means of an indirect optimization procedure, which is based on the theory of optimal control. The orbit peculiarities require that several perturbations are taken into account: an 8 × 8 model of the Earth potential is adopted and gravitational perturbations from Moon and Sun together with solar radiation pressure are considered. A procedure to guarantee convergence and define the optimal switching structure is outlined. Results concerning missions with up to 4.5 revolutions around the Earth are given, and significant features of this kind of deployment are highlighted.